Analysis of Advantages, Limitations, and Barriers of Genetic Counseling Service Delivery Models. Issue 5 (14th January 2016) - Cohen, Stephanie A.; Huziak, Rachelle C.; Gustafson, Shanna; Grubs, Robin E.
Abstract: Previous studies on genetic counseling service delivery models (SDMs) have shown that genetic counselors (GCs) are incorporating alternate models to address growing service demand and improve access to genetic services. This study sought to identify barriers, limitations and advantages to previously identified genetic counseling SDMs. A qualitative research design was employed, in which 20 practicing GCs who utilize a variety of SDMs were interviewed using an email interview format. Interview transcripts were analyzed using a thematic analysis to identify themes related to implementation and utilization of SDMs. Factors that led GCs to implement SDMs other than in‐person genetic counseling included: 1) travel distance, 2) wait time and 3) convenience. Logistical issues such as billing and reimbursement, equipment set up, making arrangements for genetic testing and the inability to see the patient are major limitations to alternative genetic counseling SDMs in clinical practice. However, GCs interviewed stated that the convenience to the patient and genetic counselor of alternative SDMs outweighed these limitations. More research is needed to assess the outcomes of SDMs in practice to demonstrate an impact on the identified barriers of travel distance, wait time and convenience.